Livro didático de História: uma análise de estrutura, abordagens e conteúdos contemporâneos - RAMOS, Adriel Eleris (2018)
The article presents results referring to the qualitative research on the didactic book of contemporary history, which was based on the analysis of the collection "History, society and citizenship", by Alfredo Boulos Junior, for primary education and one of the most widely distributed PNLD collections since its launch in 2015. Based on the data collected in the collection, the research seeks to understand how the textbook has worked on some content, how it has organized its structure, its historical approaches, its learning methodologies, images and activities, as it has inserted the transversal themes present in the contemporary curricular structure of the History discipline.